Contributors to white matter damage in the frontal lobe in Alzheimer's disease. - Chalmers, K; Wilcock, G; Love, S (2005)
Abnormalities of cerebral white matter are present in a majority of patients with Alzheimer's disease (AD) and probably contribute to motor dysfunction and cognitive impairment. The white matter abnormalities are usually attributed to degenerative vascular disease and cerebral amyloid angiopathy (CAA) but the evidence is scanty or inconclusive. In the present study we examined sections of frontal lobe from 125 autopsy-confirmed cases of AD and assessed the relationship of degenerative large and small vessel disease, CAA, parenchymal Abeta load and APOE genotype, to several objective measures of white matter damage: extent of immunolabelling for glial fibrillary acidic protein (GFAP), axonal accumulation of amyloid precursor protein (APP), axon density in superficial and deep white matter, and intensity of staining for myelin. We found no association between atherosclerosis, arteriolosclerosis, CAA or APOE genotype and white matter damage. However, labelling of white matter for GFAP correlated strongly with the parenchymal Abeta load (P = 0.0003) and with APP accumulation (P = 0.008). Our findings suggest that severity of frontal white matter damage in AD is closely related to parenchymal Abeta load and that in most cases the contribution of degenerative vascular disease, CAA and APOE is relatively minor.